FAKTOR – FAKTOR YANG MEMPENGARUHI KETEPATAN WAKTU PELAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Sella Rachmawati; Rini Rini; Yessi Fitri (Akuntabilitas, 2016)
This study aims to examine the factors that affect the timeliness of financial reporting of local government in Indonesia. These factors are divided into two major lines: factors relating to local government and politics, also the content of financial statements and managerial competence factor. Factors associated with local government and politics proxied by local independence, regional location and the election of regional heads back. Factors associated with the content of financial statements and managerial competence proxied by position and financial performance areas, audit opinion and audit findings.Samples of this study used the whole autonomous region which issued local government financial reports and audited by the Audit Board of the Republic of Indonesia as much as 524 of the total 542 local governments. They were obtained from the Audit Board of the Republic of Indonesia. Testing the hypothesis in this study used binary logistic regression. Results of this research reveals that local government and political factors that proxied by self-reliance, the regional location statistically affect the timeliness of financial reporting area in fiscal year 2013. Based on the results of logistic regression (logistic regression) showed that the factor content of the financial statements and managerial competence of government area proxied by the audit opinion and auditor's findings are statistically affect the timeliness of financial reporting area in fiscal year 2013.DOI: 10.15408/akt.v9i1.3589